Lymphatic endothelial cell-mediated accumulation of CD177+Treg cells suppresses antitumor immunity in human esophageal squamous cell carcinoma - Min Ma; Liang Li; Shu-Han Yang; Chuan Huang; Weitao Zhuang; Shujie Huang; Xin Xia; Yong Tang; Zijun Li; Zhi-Bin Zhao; Qingyun Chen; Guibin Qiao; et al. (OncoImmunology)
Regulatory T (Treg) cells are critical in shaping an immunosuppressive microenvironment to favor tumor progression and resistance to therapies. However, the heterogeneity and function of Treg cells in esophageal squamous cell carcinoma (ESCC) remain underexplored. We identified CD177 as a tumor-infiltrating Treg cell marker in ESCC. Interestingly, expression levels of CD177 and PD-1 were mutually exclusive in tumor Treg cells. CD177+ Treg cells expressed high levels of IL35, in association with CD8+ T cell exhaustion, whereas PD-1+ Treg cells expressed high levels of IL10. Pan-cancer analysis revealed that CD177+ Treg cells display increased clonal expansion compared to PD-1+ and double-negative (DN) Treg cells, and CD177+ and PD-1+ Treg cells develop from the same DN Treg cell origin. Importantly, we found CD177+ Treg cell infiltration to be associated with poor overall survival and poor response to anti-PD-1 immunotherapy plus chemotherapy in ESCC patients. Finally, we found that lymphatic endothelial cells are associated with CD177+ Treg cell accumulation in ESCC tumors, which are also decreased after anti-PD-1 immunotherapy plus chemotherapy. Our work identifies CD177+ Treg cell as a tumor-specific Treg cell subset and highlights their potential value as a prognostic marker of survival and response to immunotherapy and a therapeutic target in ESCC.